UPAYA MENINGKATKAN KEMAMPUAN MENGGUNAKAN MATA UANG MELALUI METODE BERMAIN PERAN PADA ANAK TUNAGRAHITA SEDANG KELAS X SMALB AL-AZHAR BUKITTINGGI - SRI ENDANG ASTUTI; Marlina Marlina (Universitas Negeri Padang, 2016)
Abstract. This research was conducted based on the low ability of the students with medium mental retardation in class X to use money, especially to add to subtract.They seemed to have problem in understanding abstract consept. To deal with this problem, role play method was applied. The purpose of this research was to; (1) reveal the learning process by using currency Rp.100 – Rp.10.000, and (2) to prove whether the use of role play method could increase the ability of the students with medium retardastion to use currency Rp.100 – Rp.10.000 in class X of SMALB Al-Azhar Bukittinggi.This was a Classroom Action Research which was conducted collaboratively with the classroom tercher and three students with medium mental retardation (HN,DV,and AD) in class X of SMALB Al-Azhar Bukittinggi, The data were gathered through observation, test and documentasion. The data gotten were analyzed qualitatively and quantitatively.The result of the research indicated that; 1) the learning process by using money and role play method was conducted in two cycles. Cycle I consisted of five meetings while cycle II consisted of five meetings. The respective cycle was started from planning, acting (pre-activities, whilst-activities and post-activities), observing, analyzing and reflecting, 2) The result of the learning process showed that, in the assessment phase the ability of HN and DV in adding was 20 and AD was 10, while the ability of HN and AD in subtracting was 10 and DV was 20. After role play method was applied in cycle I, the ability to use money of HN was 100, DV was 90 and AD was 80. In cycle II, the subtracting ability of HN was 80, DV was 100 and AD was 70. Based on the result of the research it was suggested to the school fellows, the teacher and the upcoming researcher to use role play method to teach the students with medium mental retardation. Key Terms; Currency, Role Play Method, Students With Medium Mental Retardation